Moving Mountains: Reform, Resistance, and Resiliency in an Appalachian Kentucky High School - Maureen K. Porter (Journal of Research in Rural Education, 1996)
The dissertation summarized below examines the question of how stakeholders in an Appalachian Kentucky high school addressed the educational problems that they targeted for reform. Set against the backdrop of the controversial Kentucky Education Reform Act of 1990 (KERA), this ethnographic investigation describes the challenges of effectively coupling top-down state mandates with bottom -up advocacy and engagement. Drawing on over a year of participant observation at "Central High School" in "Hickory County, " the research presents six connecting themes that are critical for understanding local paradigms and enduring paradoxes. Prominent in the local response was resistance to the priorities and policies set forth by the state. Although this resistance fueled the state's threats to take punitive action to encourage compliance with the standardized goals ofthe Reform Act, these threats, paradoxically, engendered greater resiliency on the part of Hickory County stakeholders to make the high school reflect their own priorities and ways of working together. Thus this research points to ways in which reform, resistance, and resiliency were entwined in this rural venue.